COVID-19 and neuropathy in type 2 diabetes - Georgios Ponirakis (803076) (2025)
This study investigated the risk factors for COVID-19 and its impact on diabetic peripheral neuropathy (DPN) in patients with type 2 diabetes (T2D). Patients with T2D underwent assessments with the NICE post-COVID questionnaire, DN4 questionnaire, vibration perception threshold (VPT), and corneal confocal microscopy (CCM) before and 11.0 ± 8.9 months after developing COVID-19. Of 76 participants with T2D, 35 (46.1%) developed COVID-19, of whom 8 (22.9%) developed severe COVID-19 and 9 (25.7%) developed long-COVID. The development of COVID-19 was associated with lower systolic blood pressure (P < 0.05). The presence and severity of DPN were not associated with developing COVID-19, severe COVID-19, or long-COVID (P = 0.42–0.94). Women were eight times more likely to develop long-COVID (P < 0.05) and elevated body weight, LDL, and VPT were associated with the development of long-COVID (P < 0.05 − 0.01). The long-COVID group exhibited significant changes in triglycerides and LDL (P < 0.05 for both) and body weight (P < 0.01) at follow-up. Their impact on clinical and neuropathy measures was comparable in patients with and without COVID-19 (P = 0.08–0.99). There was a significant reduction in corneal nerve measures (P < 0.05-0.0001) in patients with and without COVID-19. A low systolic blood pressure, altered lipids, body weight, higher VPT, and gender may determine the impact of COVID-19 in patients with T2D, but there was no evidence of an impact of COVID-19 on the development or progression of DPN. Other Information Published in: Scientific Reports License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1038/s41598-025-95133-4